Thermophilic Geobacillus galactosidasius sp. nov. loaded γ-Fe2O3 magnetic nanoparticle for the preconcentrations of Pb and Cd. (February 2016) - Özdemir, Sadin; Kılınç, Ersin; Okumuş, Veysi; Poli, Annarita; Nicolaus, Barbara; Romano, Ida
Graphical abstract: Highlights: Thermophilic bacteria, Geobacillus galactosidasius sp nov. was used as biosorbent. It was loaded on γ-Fe2 O3 magnetic nanoparticle. Pb and Cd were preconcentrated. The method was validated through the analysis of certified and standard sample. SEM–EDX was employed for investigations of surface morphology. Abstract: Thermophilic bacteria, Geobacillus galactosidasius sp nov. was loaded on γ-Fe2 O3 magnetic nanoparticle for the preconcentrations of Pb and Cd by solid phase extraction before ICP-OES. pH and flow rate of the solution, amounts of biosorbent and magnetic nanoparticle, volume of sample solution, effects of the possible interferic ions were investigated in details. Linear calibration curves were constructed in the concentration ranges of 1.0–60 ng mL −1 for Pb and Cd. The RSDs of the method were lower than 2.8% for Pb and 3.8% for Cd. Certified and standard reference samples of fortified water, wastewater, poplar leaves, and simulated fresh water were used to accurate the method. LOD values were found as 0.07 and 0.06 ng mL −1 respectively for Pb and Cd. The biosorption capacities were found as 34.3 mg g −1 for Pb and 37.1 mg g −1 for Cd. Pb and Cd concentrations in foods were determined. Surface microstructure was investigated by SEM–EDX.